Edukasi Penyuluhan Mental Health terhadap Pengetahuan Remaja di SMA Inshafuddin Banda Aceh - Dewi Sartika (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
Teenager who has good mental health condition are aware of his/her ability to overcome normal stress life with good information knowledge. Good mental health in teenager does not involve closed responses and negative emotions in giving opinions. This research aimed to determine the influence of mental health outreach onon teenagers’ knowledge and attitude at Inshafuddin Senior High School of Banda Aceh. This research was a quasy experiment with one group pretest and post test reserach design. The population of this research was 200 female students, and 50 respondents were taken as the samples of the research using a non-probability sampling technique. This research was conducted from February 7 to 13, 2024. The research novelty of this research was the researcher gave more focus on the teenagers’ mental health, in which the outreach was performed through Poer Point-Based. The previous research used a leaflet. The statistic test result showed that the equal variances assumed of knowledge variable showed the t value of -6,849, Therefore, it was concluded that health outreach regarding mental health is an essential aspect for teenagers to understand. It was recommended to the schools to involve authorized agencies such as the mental hospitals to hold regular outreach in preventing the mental health issue among teenagers.